2017
DOI: 10.1590/0102-311x00038516
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao aleitamento cruzado em duas cidades do Sudeste do Brasil

Abstract: Resumo O objetivo foi estimar a prevalência de aleitamento cruzado em duas cidades brasileiras e analisar os fatores associados à prática. Estudo transversal aninhado a uma coorte de gestantes recrutadas nas unidades públicasEste é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições, desde que o trabalho original seja corretamente citado.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…It is indicated that the mother who has some difficulty in breastfeeding looks for a health professional to be guided and, if she is not yet able to breastfeed, she should go to a Human Milk Bank (HMB) because she receives treated and pasteurized baby donated milk, eliminating any chance of transmission of diseases to the child. 11 Another controversy arose about breastfeeding: whether or not it avoids a new pregnancy, and the results were proportional, because half felt that yes and the rest did not. Consideration should be given to several aspects that will depend on exclusive and ondemand breastfeeding.…”
Section: Resultsmentioning
confidence: 99%
“…It is indicated that the mother who has some difficulty in breastfeeding looks for a health professional to be guided and, if she is not yet able to breastfeed, she should go to a Human Milk Bank (HMB) because she receives treated and pasteurized baby donated milk, eliminating any chance of transmission of diseases to the child. 11 Another controversy arose about breastfeeding: whether or not it avoids a new pregnancy, and the results were proportional, because half felt that yes and the rest did not. Consideration should be given to several aspects that will depend on exclusive and ondemand breastfeeding.…”
Section: Resultsmentioning
confidence: 99%
“…28 However, it was observed in the study that given the impossibility of being with their children, puerperal women would choose to use this tool. Furthermore, the absence of a bottle was linked to cross-breastfeeding, revealing a lack of knowledge about the dangers related to this practice, which should be avoided considering the risk of vertical transmission of diseases to newborns, with HIV/AIDS, 29 presents as an important demand for learning to be explored by health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Já Seehausen et al (2017), também mostrou que a maior parte foram orientadas sobre aleitamento materno (78,7%), se autodeclararam não brancas (73,5%) e não trabalhavam (63,2%). Contudo, 22,7% eram adolescentes e 77,6% tinham ensino fundamental incompleto.…”
Section: Discussionunclassified
“…Estudos verificaram a relação de características como idade entre 21 a 30 anos, raça não branca, baixa renda, médio nível de escolaridade e não exercício de atividade remunerada como fatores prevalentes, confirmando associação de indicadores de vulnerabilidade com a prática de aleitamento cruzado (Seehausen et al, 2017;Can;Ünülü, 2019).…”
Section: Discussionunclassified